PENGARUH PENDIDIKAN KESEHATAN MANFAAT HEMODIALISA TERHADAP MOTIVASI HARAPAN HIDUP PADA PASIEN GAGAL GINJAL KRONIK DI RUMAH SAKIT UMUM DAERAH H. SAHUDIN KOTA CANE TAHUN 2021 - Kristina; Kamaliah Ainun; Srimis Leini Saragih (Jurnal Ilmiah Keperawatan IMELDA, 2021)
Hemodialysis is a process carried out to remove fluids and waste products from the body when the kidneys are no longer able to carry out the process. The purpose of the study was to analyze "the effect of health education on the benefits of hemodialysis on motivation for life expectancy in patients with chronic kidney failure at the H. Sahudin Regional General Hospital, Cane City in 2021. This research is an experimental study that uses parametric statistical analysis, namely the statistical section whose parameters from the population follow a certain distribution. The research design uses Pre-Experimental Design with a one-group pretest-posttest design approach, which is a technique to determine the effect before and before giving treatment. Based on the results of this study, family motivation in patients undergoing hemodialysis at the Cane City Hospital was mainly in the moderate category. Quality of life in patients undergoing hemodialysis well, there is a relationship between family motivation and quality of life of patients undergoing hemodialysis. Results based on conclusions and suggestions. Family motivation for patients undergoing hemodialysis at the Cane City Hospital is the most important in the moderate category. It is hoped that the motivation that has been given to hemodialysis patients and families who are still low in providing motivation to increase their motivation to family members undergoing hemodialysis is expected.